2004
DOI: 10.1016/j.biomaterials.2004.01.053
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wear particles in the expression of osteoclastogenesis factors by osteoblasts

Abstract: Orthopedic implant failures are often associated with peri-implant osteolysis. Particles generated from the wear process have been suspected to play an important role in this situation. Indeed, the peri-implant osteolysis could be due to the presence of particles stimulating the osteoclastogenesis process. We hypothesize then that the presence of a low particle concentration positively influences osteoblasts to produce osteoclastogenesis factors. If true, this hypothesis would then support the idea that the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] Mature osteoblastic cell lines (e.g., MG-63 osteoblasts) challenged with metallic or polymeric particles show reduced proliferation, viability, collagen synthesis, and matrix mineralization, as well as elevated secretion of osteolysis-inducing factors such as IL-6 and PGE 2 . [7][8][9][10][11] Human mesenchymal stem cells challenged with titanium particles in osteogenic medium also show reduced proliferation, viability, collagen synthesis, and matrix mineralization. [3][4][5] Our group has previously demonstrated that murine bone marrow osteoprogenitor cells challenged with polymethylmethacrylate (PMMA) particles on the first day of differentiation show a dose-dependent decrease in the expression of osteoblastic phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11] Mature osteoblastic cell lines (e.g., MG-63 osteoblasts) challenged with metallic or polymeric particles show reduced proliferation, viability, collagen synthesis, and matrix mineralization, as well as elevated secretion of osteolysis-inducing factors such as IL-6 and PGE 2 . [7][8][9][10][11] Human mesenchymal stem cells challenged with titanium particles in osteogenic medium also show reduced proliferation, viability, collagen synthesis, and matrix mineralization. [3][4][5] Our group has previously demonstrated that murine bone marrow osteoprogenitor cells challenged with polymethylmethacrylate (PMMA) particles on the first day of differentiation show a dose-dependent decrease in the expression of osteoblastic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Osteolysis occurs when inflammatory cells activated by particulate wear debris release cytokines that promote the differentiation and activity of osteoclasts. 1,2 The chronic exposure of osteoprogenitors and mesenchymal stem cells in the bone marrow to wear debris may also result in impaired bone formation through the suppression of osteoblastic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In response to wear particle stimulation, osteoblast ability to secrete osteoid is impaired [41], and collagen I synthesis is decreased [46]. Additionally, wear particles induce production of IL-1, IL-6, IL-8, TNF-a, CCL2, and MMP1 in osteoblasts [41,46], in addition to osteoclastogenesis factors, RANKL and M-CSF [47].…”
Section: Implant-induced Inflammatory Complicationsmentioning
confidence: 99%
“…While it is widely accepted that macrophages play a pivotal role in osteoclastogenesis (Takayanagi, 2010), the formation of osteoclasts in response to wear particles is highly reliant on RANKL (Receptor activator of nuclear factor kappa-B ligand) (Clohisy et al, 2003, Liu et al, 2009. RANKL expression was up-regulated in both primary human osteoblasts and in hFOB1.19 cells (human fetal osteoblastic cell line) upon stimulation with titanium particles (Cadosch et al, 2010, Pioletti andKottelat, 2004). Moreover, in vivo osteolysis models revealed that the osteoclast number is increased in response to titanium particles, with a higher expression of TRAP (tartrate-resistant acid phosphatase; osteoclast marker) and RANKL in the tissue surrounding the implantation site (Jiang et al, 2013b, Shin et al, 2012.…”
Section: 1immune Response To Titaniummentioning
confidence: 99%